Screening Phytocompounds of Tinospora cordifolia to Find Potential Drug Targets for Cystic Fibrosis - Saumya Singh (International Journal of Genetic Modifications and Recombinations, 2025)
This study aimed to evaluate the therapeutic potential of phytocompounds derived from Tinospora cordifolia in treating cystic fibrosis (CF), a genetic disorder caused by mutations in the CFTR gene that lead to severe respiratory and digestive complications. Phytocompounds were retrieved from the IMPPAT database and subjected to molecular docking simulations using PyRx to assess their binding affinity to the CFTR protein. The top-scoring compounds – sterol, magnoflorine, tembetarine, kaempferol, and tinosporinone – were identified based on their strong interaction with the target protein. To evaluate their suitability as drug candidates, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) analysis was performed. Results revealed that all five compounds demonstrated favorable pharmacokinetic and pharmacodynamic properties, including high gastrointestinal absorption, good bioavailability, and low predicted toxicity. Additionally, the compounds satisfied essential drug-likeness criteria, highlighting their potential for therapeutic application. These findings underscore the promise of Tinospora cordifolia phytocompounds as a natural source for CF drug development. However, while the In silico approach provides a strong basis, further validation through in vitro and in vivo studies is necessary to confirm their biological activity and clinical relevance. This study highlights the role of bioinformatics in discovering plant-based treatments for genetic disorders like CF.
Keywords: ADMET analysis; CFTR; Tinospora Cordifolia; cystic fibrosis; drug-likeness; molecular docking; phytocompounds